Dolomedes fishing spider biology: gaps and opportunities for future research - Yu, Kuang-Ping; Roithmair, Zita; Kurovski, Jillian; Connolly, Simon J.; Vink, Cor J.; Johnson, James Chadwick; Kralj-Fišer, Simona; Kuntner, Matjaž; Hebets, Eileen A.; Painting, Christina J. (Frontiers in Arachnid Science, 2024)
Dolomedes may easily be considered to be among the most charismatic spider taxa. Known colloquially as fishing or raft spiders, this clade of dolomedid cursorial hunters is speciose with about 100 valid species names. Most Dolomedes are large spiders that inhabit water bodies across all continents except Antarctica and, interestingly, South America. Dolomedes have captured the attention of researchers and the public alike for their ability to walk on and submerge under water, fish for prey (including small vertebrates), and for their often-bizarre mating behavior that includes examples of male spontaneous death and sexual cannibalism. In this review, we critically evaluate what is known of Dolomedes biology, focusing on their systematics and morphology, ecology, behavior, and conservation. Given their close association with water, Dolomedes may be particularly vulnerable to the impacts of anthropogenic change and provide an important group of indicator species for understanding the effect of pollution, habitat loss and climate change. We outline a roadmap for future studies that, in our view, will consolidate Dolomedes as an ideal model lineage among spiders for addressing a vast array of questions across multiple fields of biology.